2021
DOI: 10.1016/j.brs.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional and state-dependent modulation of brain activity by transcranial focused ultrasound in non-human primates

Abstract: Transcranial focused ultrasound (FUS) stimulation under MRI guidance, coupled with functional MRI (fMRI) monitoring of effects, offers a precise, noninvasive technology to dissect functional brain circuits and to modulate altered brain functional networks in neurological and psychiatric disorders. Here we show that ultrasound at moderate intensities modulated neural activity bi-directionally. Concurrent sonication of somatosensory areas 3a/3b with 250 kHz FUS suppressed the fMRI signals produced there by perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 62 publications
3
51
1
Order By: Relevance
“…Thus, the difference in ultrasoundevoked responses detected in the hippocampus and the motor cortex is due to brain-region-specific tissue properties. Recently fMRI studies in nonhuman primates showed that focused ultrasound stimulation of somatosensory cortex produces either excitatory or inhibitory effects in the brain depending on the activity states of the somatosensory pathway (Yang et al, 2021). Our observation of brain-region-specific ultrasound neuromodulation effect further highlights that neural circuit properties are critical consideration in ultrasound neuromodulation.…”
Section: Pre Postsupporting
confidence: 51%
See 2 more Smart Citations
“…Thus, the difference in ultrasoundevoked responses detected in the hippocampus and the motor cortex is due to brain-region-specific tissue properties. Recently fMRI studies in nonhuman primates showed that focused ultrasound stimulation of somatosensory cortex produces either excitatory or inhibitory effects in the brain depending on the activity states of the somatosensory pathway (Yang et al, 2021). Our observation of brain-region-specific ultrasound neuromodulation effect further highlights that neural circuit properties are critical consideration in ultrasound neuromodulation.…”
Section: Pre Postsupporting
confidence: 51%
“…In rodents, several studies demonstrated that ultrasound directed to the motor cortex can successfully elicit muscle responses (Li et al, 2016;Lee et al, 2018;King et al, 2013). In humans and nonhuman primates, ultrasound can effectively stimulate somatosensory receptors in the hand and modulate responses in the somatosensory cortex and other brain regions (Gavrilov et al, 1976;Legon et al, 2012Legon et al, , 2014Lee et al, 2015Lee et al, , 2016Yang et al, 2018Yang et al, , 2021Kim et al, 2017;Yuan et al, 2020). These studies, though providing convincing evidence that ultrasound can modulate neural activity in intact brain circuits, rely largely on recording downstream motor activations via electromyography (EMG) or aggregated neural signals, such as electroencephalogram (EEG), functional magnetic resonance imaging (fMRI), and functional near-infrared spectroscopy (fNIR), which are either indirect measures of neural activity or have poor spatiotemporal resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the study suggests that different neurons respond differently to tFUS stimuli and indicates further parametric studies should pay attention to the regulation of neural activity at the cell level ( Wattiez et al, 2017 ). Yang et al (2021) reported that medium amplitude tFUS (425 kPa free-field at 250 kHz) in the macaque brain modulated the activity of neurons at the target in dual directions (excitation and suppression). This simultaneous excitatory and suppressive neuromodulation may be mediated by activation of large excitatory pyramidal and small inhibitory interneurons, respectively.…”
Section: Evidence For Mechanismsmentioning
confidence: 99%
“…Neurophysiological studies implicate the striatum in reward-modulated sensory-motor decision making (Ding & Gold, 2013;Fan et al, 2020. ) Previous studies in macaques have shown that FUS can temporarily enhance neural activity and connectivity to closely related areas in both cortical and subcortical structures (Verhagen et al, 2018;Yang et al, 2021). FUS can also directly affect behavior in rhesus macaques.…”
Section: /33mentioning
confidence: 96%